Conceptualising the role of opinion leaders as moderator to local communities commitment in corporate social responsibility (CSR) communication - Rehan Tariq; Izzal Asnira Zolkepli; Mahyuddin Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2022)
The concept of communication as mediation has now become a crucial metric for analysing various behavioural patterns, particularly in relation to new media. Several psychological and structural factors interpreting the relationship between engagement and the consumption of information and cognitive processes have been emphasised through the use of O-S-O-R and O-S-R-O-R communication mediation models. However, there remains a variety of viewpoints concerning theoretical perspectives and thematic patterns, leading to difficulties in obtaining a structured overview and so advance the development of communication mediation research. This study consists of a systematic literature review of 739 articles, published between 2015 and 2020, across three databases, Scopus, Google Scholar and EBSCOhost, resulting in thirty-four being identified as usable for providing a synthesis of current knowledge focusing on new media. This highlights a considerable variation in existing constructions and trends, along with communication effects and O-S-R-O-R measures. This review undertakes a thematic classification of prior studies in order to: firstly, identify key gaps in the literature, secondly, identify potential areas for additional research, and thirdly, offer recommendations for future studies. By offering an in-depth analysis, this review will enhance information and assist scholars to expand the existing literature. In addition, this study examines the implications for the investigation of potential pre-emptive factors for O-S-O-R and O-S-R-O-R.